Pengembangan Strategi Komunikasi dan Pelatihan Karyawan Sebagai Upaya Meningkatkan Kinerja Karyawan di PT. Jasa Peralatan Pelabuhan Indonesia - Furqon, Muhammad; Sutrisno (Program Studi Administrasi Bisnis, 2024)
A company's competitiveness is not just about survival but also about creating sustainable advantages to seize greater opportunities in the global market. Therefore, companies must continuously innovate, understand consumer needs, and enhance efficiency to maintain competitiveness. Employee performance plays a critical role in the success and sustainability of a company. Thus, companies must consistently invest in training, development, and fostering a supportive work environment to enable employees to perform at their best. This study examines the development of communication strategies and employee training as efforts to improve employee performance at PT. Jasa Peralatan Pelabuhan Indonesia, utilizing a quantitative-based research method. The study population consisted of 547 individuals, but through the Random Sampling method, a sample of 85 participants was obtained using the Slovin formula. The research analyzes data using SPSS version 25.0 with a multiple linear regression approach. The results revealed that, partially, the communication variable has a positive and significant influence on employee performance. Similarly, the employee training variable shows a significant influence on employee performance. Collectively, communication and employee training significantly impact employee performance. Keywords: Strategy Development, Communication, Employee Training, Employee Performance